Achievements And Shortcomings in The Oil and Gas Field During the Years Of Independence (Zien Journal of Social Sciences and Humanities, 2024)
This article presents an analytical analysis of our country's achievements in the field of oil and gas during the years of independence, development prospects, shortcomings and future plans. Statistical and comparative discussion is carried out in the article.